2022
DOI: 10.3389/fonc.2022.872814
|View full text |Cite
|
Sign up to set email alerts
|

A computed tomography-based preoperative risk scoring system to distinguish lymphoepithelioma-like gastric carcinoma from non-lymphoepithelioma-like gastric carcinoma

Abstract: PurposeThe aim of this study was to develop a preoperative risk scoring model for distinguishing lymphoepithelioma-like gastric carcinoma (LELGC) from non-LELGC based on contrast-enhanced computed tomography (CT) images.MethodsClinicopathological features and CT findings of patients with LELGC and non-LELGC in our hospital from January 2016 to July 2022 were retrospectively analyzed and compared. A preoperative risk stratification model and a risk scoring system were developed using logistic regression.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…34 GLELC has special pathological characteristics, including stromal and intense lymphocytic infiltration. 35 In addition to being associated with EBV infection, another pathological type of GLELC is microsatellite instability (MSI)-high tumors. 36 Min et al revealed that EBV infection could serve as an independent predictor of survival in patients with LELC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 GLELC has special pathological characteristics, including stromal and intense lymphocytic infiltration. 35 In addition to being associated with EBV infection, another pathological type of GLELC is microsatellite instability (MSI)-high tumors. 36 Min et al revealed that EBV infection could serve as an independent predictor of survival in patients with LELC.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoepithelioma‐like gastric carcinoma is a rare type of EBVaGC that was first reported in 1976 34 . GLELC has special pathological characteristics, including stromal and intense lymphocytic infiltration 35 . In addition to being associated with EBV infection, another pathological type of GLELC is microsatellite instability (MSI)‐high tumors 36 .…”
Section: Discussionmentioning
confidence: 99%